Early and late human capital investments, borrowing constraints, and the family - Elizabeth M. Caucutt; Lance Lochner (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
We develop a dynastic human capital investment framework to study the importance of potential market failures - family borrowing constraints and uninsured labor market risk - as well as the process of intergenerational ability transmission in determining human capital investments in children at different ages. We explore the extent to which policies targeted to different ages can address these market failures, potentially improving economic efficiency and equity. We show that dynamic complementarity in investment and the timing of borrowing constraints are critical for the qualitative nature of investment responses to income and policy changes. Based on these analytical results, we use data from the Children of the NLSY (CNLSY) to establish that borrowing constraints bind for at least some families with young and old children. Calibrating our model to fit data from the CNLSY, we find a moderate degree of dynamic complementarity in investment and that 12% of young and 14% of old parents borrow up to their limits. While the effects of relaxing any borrowing limit at a single stage of development are modest, completely eliminating all lifecycle borrowing limits dramatically increases investments, earnings, and intergenerational mobility. Additionally, the impacts of policy or family income changes at college-going ages are substantially greater when anticipated earlier, allowing early investments to adjust. Finally, we show that shifting the emphasis of investment subsidies from college-going ages to earlier ages increases aggregate welfare and human capital.
Keywords: 330